2018
DOI: 10.1016/j.brainres.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of early-onset motor deficits in the Pink1−/− mouse model of Parkinson disease

Abstract: In Parkinson disease (PD), a complex neurodegenerative disorder that affects nearly 10 million people worldwide, motor skills are significantly impaired. However, onset and progression of motor deficits and the neural correlates of these deficits are poorly understood. We used a genetic mouse model of PD (Pink1-/-), with phenotypic similarities to human PD, to investigate the manifestation of early-onset sensorimotor deficits. We hypothesized this mouse model would show early vocalization and gross motor dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…Consistent with our results, deficits in fine motor coordination were reported in one previous characterization of Parkin knockout mice generated by targeted deletion of exon 3 [ 17 ]; however, in another independently generated exon 3 deleted knockout model, no motor deficits were reported although these mice exhibited learning and memory deficits [ 28 ]. More recently, similar fine motor deficits were found in Pink1 knockout mice in the absence of nigrostriatal degenerative pathology [ 29 ], further underscoring the importance of performing more sensitive behavioural testing in mouse models of PD. In our study, we were unable to determine the age-of-onset of the motor deficits, although it was reported that Pink1 knockout mice take approximately six months to exhibit detectable locomotor dysfunction [ 29 ].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistent with our results, deficits in fine motor coordination were reported in one previous characterization of Parkin knockout mice generated by targeted deletion of exon 3 [ 17 ]; however, in another independently generated exon 3 deleted knockout model, no motor deficits were reported although these mice exhibited learning and memory deficits [ 28 ]. More recently, similar fine motor deficits were found in Pink1 knockout mice in the absence of nigrostriatal degenerative pathology [ 29 ], further underscoring the importance of performing more sensitive behavioural testing in mouse models of PD. In our study, we were unable to determine the age-of-onset of the motor deficits, although it was reported that Pink1 knockout mice take approximately six months to exhibit detectable locomotor dysfunction [ 29 ].…”
Section: Resultsmentioning
confidence: 79%
“…More recently, similar fine motor deficits were found in Pink1 knockout mice in the absence of nigrostriatal degenerative pathology [ 29 ], further underscoring the importance of performing more sensitive behavioural testing in mouse models of PD. In our study, we were unable to determine the age-of-onset of the motor deficits, although it was reported that Pink1 knockout mice take approximately six months to exhibit detectable locomotor dysfunction [ 29 ].
Figure 3.
…”
Section: Resultsmentioning
confidence: 79%
“…We tested the specific hypotheses that Pink−/− female rats would demonstrate impaired limb motor and vocal performance with increased anxiety and anhedonia, and that changes which would become more pronounced with disease progression. The statistical analysis was designed to account for body weight; Pink1−/−rats are consistently heavier compared to controls [30,31]. Finally, estrous phase appeared to be an important variable for the number of calls produced within a testing session, but did not interact with other limb motor, acoustic, anhedonia, or anxiety behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The Pink1−/− rat model replicates the progression of PD through both preclinical and mid-symptomatic phases, displaying characteristic features such as early-onset, slow progression of sensorimotor deficits, and brainstem neuropathology [28]. Previous research has extensively assayed this model for limb motor deficits as well as ultrasonic vocalization and swallowing deficits [29][30][31][32][33][34][35]. An additional consideration in the Pink1−/− rat model is the acknowledgement of sex-differences in research designs and the resulting potential sex-biased results, as primary research using the Pink1−/− rat model has been done exclusively in males.…”
Section: Introductionmentioning
confidence: 99%
“…Using the high‐frequency‐modulated call results, baseline and 1 WPS were chosen for additional in depth analysis as follows: a trained reviewer independently classified and quantified all calls in a blinded fashion within the first 90 s after the first detected call. Ten call types (i.e., constant, downsweep, upsweep, harmonic, multiple jumps, jump up, jump down, half cycle, full cycle, and two cycle) were identified and grouped accordingly into four call categories based on complexity: simple, complex, jump, and cycle (Figure ) (Grant et al, ; Kelm‐Nelson et al, ). The following acoustic properties that are common in communication signals among various species, including mice and humans, were measured for each call type and category (Basken, Connor, & Ciucci, ): percentage of call type (%), bandwidth (kHz), peak frequency (kHz), duration (ms), and duration of peak frequency (ms).…”
Section: Methodsmentioning
confidence: 99%